Gestión administrativa del fondo de cesantía del magisterio ecuatoriano FCME 2021 - Olvera Montero, Jomira Stefania (2022)
Nowadays, administrative management within a company is considered as a primary task to be carried out and fulfilled through the execution of various activities aimed at coordinating all available resources to meet the established objectives. In the present investigation entitled "The Administrative Management of the Ecuadorian Teacher's Severance Fund Fcme 2021 of the city of Babahoyo, has as a general objective to analyze the impact of administrative management on the Ecuadorian Teacher's Severance Fund, 2021 with the purpose of taking actions to increase profitability. The correct use of its resources allows the company to have adequate tools, processes and activities for business strengthening and corporate improvement, administrative processes and competitive strategies are essential elements in the development of the company. company for decision making and good management of the company.